Hubungan Usia Gestasi Dan Paritas Dengan Kejadian Hiperemesis Gravidarum Pada Ibu Hamil Di Wilayah Kerja Puskesmas Pasar Manna Kabupaten Bengkulu Selatan - Rahmi, Nadia Sri; Rahmarianti, Gusni; Veronica, Nora (Jurnal Kebidanan Manna, 2023)
Hyperemesis gravidarum is a disease that is quite dangerous for maternal health if it lasts for a long time and causes symptoms of nausea and vomiting that cause weight loss, as well as metabolic disorders that can cause complications such as malnutrition, weakness, and dehydration in the mother. Gestational age is one of the risk factors for hyperemesis gravidarum; it is related to the levels of chorionic gonadotropin, oestrogen, and progesterone in the mother's blood. In addition, the parity factor is also associated with the condition of hyperemesis gravidarum in pregnant women due to the mother's psychological condition. This study aims to determine the relationship between gestational age and parity with the incidence of hyperemesis gravidarum in the Pasar Manna Health Centre working area, South Bengkulu Regency. This research is an analytical study with a cross-sectional design. The population of this study was all pregnant women in the work area of the Pasar Manna Health Centre, South Bengkulu Regency, in May 2023, totaling 217 people with a sample of 68 people. Data analysis was done with a chi-square test. The results showed that most of the pregnant women with gestational age TM II had parity > multipara (58.8%) and not hyperemesis gravidarum (61.8%). Statistical tests for the variable gestational age and the incidence of hyperemesis gravidarum obtained a value of ρ (0.000) <α (0.05), and for the variable parity with the incidence of hyperemesis gravidarum obtained a value of ρ (0.015) <α (0.05). In conclusion, there is a significant relationship between gestational age and parity and the incidence of hyperemesis gravidarum in the working area of Puskesmas Pasar Manna, South Bengkulu Regency.